Analysis of Digital Emotional Branding Strategies and Their Influence on Enhancing Consumer Loyalty in the Online Culinary Industry - Mourinho, Tiago; Alvaro, Kenzo (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
The digital transformation of the online culinary industry has significantly reshaped how brands build emotional connections with their consumers. This study aims to analyze the influence of digital emotional branding on enhancing consumer loyalty within Indonesia’s online culinary industry. Employing a mixed-methods sequential explanatory design, this research integrates quantitative data from 100 survey respondents and qualitative insights from 10 key informants, obtained through in-depth interviews. Quantitative data were analyzed using SPSS 26 to assess the relationship between emotional branding and loyalty. In contrast, qualitative data were analyzed using NVivo 12 Plus to identify emotional themes, including digital intimacy, brand narrative authenticity, and consumer attachment. The findings reveal that digital emotional branding has a positive and significant effect on consumer loyalty. Consumers tend to remain loyal to brands that create authentic emotional experiences through engaging and interactive digital content. This study contributes to the development of emotion-based digital marketing theory and offers practical implications for online culinary businesses to strengthen personalized, meaningful digital communication strategies. Overall, the study underscores that the success of digital culinary brands depends not only on product quality but also on their ability to foster deep emotional bonds with consumers in the digital space.